The Impact of Groupthink, Group Cohesiveness, and Bounded Rationality on the Quality of Decision Making: A Systematic Literature Review - Pratiwi, Retno; Wening, Nur (Graduate Program Magister Manajemen Pendidikan, 2024)
This research conducted a systematic literature review of the impact of groupthink, group cohesiveness, and bounded rationality on group decision making. Through a systematic analysis method of relevant literature, the research results reveal that the interaction between these three factors significantly influences the quality of the group decision-making process. The novelty of this research lies in the integration of these three factors in one conceptual framework, providing holistic insights that can be the basis for developing more effective strategies in improving the quality of group decision making. The contribution of this research is important in the social psychology and group decision-making literature, highlighting practical implications for improving decision-making processes in group contexts.